Emotional Regulation Scale: A Rasch Model Approach - Muqaffi; Nandang Rusmana; Ilfiandra (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
This study evaluates students' emotion regulation ability during the first three years of study with a qualitative experimental approach in a within group design. The instrument used was James J. Gross' Emotion Regulation, which was translated into Bahasa Indonesia. This instrument includes two main aspects: Cognitive Reappraisal (6 items) and Expressive Suppression (4 items), with a total of 10 items. The validity and reliability of the instrument were tested using Rasch modeling through the Winsteps application. The results of the validity analysis showed 8 items were valid and 2 items required revision. Instrument reliability was measured by Cronbach's Alpha, resulting in a value of 0.79 (Good category) for the overall instrument, and a value of 0.97 (Excellent category) for item reliability. These validity and reliability tests ensure that the data collected is accurate, consistent, and reliable, so that this instrument can be used to measure students' level of emotion regulation. Keywords: emotional regulation, rasch model, emotional regulation scale, college students